P001 CHARACTERIZING CURRENT TREATMENT AND GAPS IN THE INFLAMMATORY BOWEL DISEASE POPULATION IN A LARGE INTEGRATED HEALTHCARE SYSTEM IN NORTHERN CALIFORNIA. (7th February 2019) - Li, Jinnan; Mudiganti, Satish; Martinez, Meghan; Hsu, Ronald; LaMori, Joyce; Bibeau, Wendy; Pressman, Alice
Abstract: Introduction: Crohn's disease (CD) and ulcerative colitis (UC), two major types of inflammatory bowel disease (IBD), affect as many as 1.6 million Americans. IBD is a chronic relapsing illness, where effective and efficient care requires seamless coordination of primary care providers, gastroenterologists, and caretakers, coupled with engaged and activated patients. We sought to understand the IBD patient population, to identify gaps in care, and ultimately develop a foundation for personalized patient care by analyzing patient characteristics, symptoms, and medications over a 5-year period using Electronic Health Record (EHR) data from a large integrated healthcare system in Northern California. Methods: All adult primary care (PC) patients who had one or more diagnoses of CD (ICD-9 555/ICD-10 K50) or UC (ICD-9 556/ICD-10 K51) associated with outpatient office visit or hospitalization encounters were identified as possible IBD cases. We defined incident-IBD care as first IBD-coded encounter occurring at least 270 days after the first PC encounter. We categorized IBD medications into 4 groups: 5-Aminosalicyclic-Acid (5-ASA) (G1), Steroids (G2), immunomodulators (G3), and biologics (G4). We used descriptive statistics to describe how symptoms and IBD-specific medications varied among those incident cases during pre- and post-diagnosis periods. Results: Among 1, 444, 711 adult PC patients, 4009 (0.3%) were coded as CD, 5873 (0.4%) as UC, and 479 (5%) of these were coded as both. We identified 728 and 1139 patients as incident CD and UC cases, respectively. Tables 1-2 display demographic characteristics for all IBD patients and incident IBD patients, respectively. 48% of incident IBD patients (CD/UC) had at least one of the 5 common IBD symptoms (diarrhea, abdominal pain/cramping, blood in stool, unintended weight loss, reduced appetite) indicated by ICD diagnosis codes in the EHR prior to the IBD diagnosis. However, among those who had at least 2 encounters with IBD diagnosis codes, only 5% of incident CD patients and 8% of incident UC patients still had at least one of the 5 symptoms recorded at their 2 nd visit after IBD diagnosis. Approximately 1/4 of incident IBD patients had orders placed for IBD-specific medications on or after diagnosis over a mean 32-month period as follows: CD cases: G1-10%, G2-5%, G3-5%, G4-5%; UC cases: G1-21%, G2-4%, G3-4%, G4-2%. Discussion: Similar to many published US estimates, we identified more UC than CD in our healthcare system. Nearly half of incident IBD patients had documented symptoms at diagnosis, but symptoms were not reported at follow-up in most cases. Only a quarter received orders for IBD-specific drugs, with 5-ASAs the most commonly prescribed medication for both conditions. Future work includes further understanding why medication orders are lower than expected and the reasons behind this potential gap in care.